Undetactable levels of genotoxicity of SiO2 nanoparticles in in vitro and in vivo tests [Erratum] - Kwon JY (Dove Medical Press, 2015)
Kwon JY, Kim HL, Lee JY, et al. Int J Nanomedicine. 2014;9(Suppl 2):173–181.The title of the paper “Undetactable levels of genotoxicity of SiO2 nanoparticles in in vitro and in vivo tests” should read “Undetectable levels of genotoxicity of SiO2 nanoparticles in in vitro and in vivo tests”.Read the original article